Semantic basis of verbal word-building (on the materials of verbal nouns) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
Semantic basis of creation of verbal nouns is described in the article, the phenomena of transformation of judicial value are analysed in subject.
Keywords: metonymy; verbal nouns; judicial value; metonymical transfers